RANCANG BANGUN SISTEM TRACER MEDICAL RECORD PASIEN RAWAT JALAN BERBASIS WEB DI RUMAH SAKIT UMUM PRIMA MEDIKA DENPASAR - Landina, Made; Kartiko, Bambang Hadi; Karsana, I Wayan Widi (ARCHIVE OF COMMUNITY HEALTH, 2023)
ABSTRACTThe application of the Web-based Outpatient Tracer Medical Record system at Prima Medika General Hospital Denpasar aims to help track medical records that come out of storage and help reduce the occurrence of missfiles. At present the use of Medical Record tracers still uses a manual system, tracers that are used as markers or as medical record trackers that are removed from storage racks still use cardboard paper so that they are easily damaged, besides that the writing of the name of the borrower's medical record is still written manually, causing the writing of the borrower's name it is not clearly visible and outpatient medical record storage is not provided with an expedition book to write the name of the medical record borrower. This study uses the system development life cycle (SDLC) design method with the stages of planning, analysis, design, implementation. Meets the usability standard, namely 77.33% can be classified as “Appropriate” and this study succeeded in creating a web-based Tracer Medical Record design at Prima Medika General Hospital Denpasar with service features Borrowing Medical Records, Distribution of Medical Records, and Return of Medical Records. can help Medical Record officers to facilitate borrowing outpatient Medical Records in a computerized system.Keywords: Tracer Medical Record, Loans, Distribution, Returns, RSU Prima Medika